Crystal Structure and Infrared Spectroscopy of trans-[Cr(NCS)2(Me2tn)2][Cr(NCS)4(Me2tn)] Moiety - Moon, Dohyun; Choi, Jong-Ha (Asian Journal of Chemistry, 2021)
A novel double complex, trans-[Cr(NCS)2(Me2tn)2][Cr(NCS)4(Me2tn)]·NaSCN·i-PrOH, (1) (Me2tn = 2,2-dimethyl-1,3-propanediamine, C5H14N2; i-PrOH = isopropyl alcohol), was prepared and its structure was determined by single-crystal X-ray diffraction at 95 K. The complex 1 crystallized in the space group P`1 of the triclinic system with two nuclear formula units in a cell of dimensions a = 13.220(3), b = 13.699(3), c = 15.087(3) Å and α = 116.193(3), β = 102.73(3) and γ = 104.48(3)°. X-ray structural analysis revealed two crystallo-graphically independent Cr(III) complex cations in the complex 1. The asymmetric unit contains two halves of trans-[Cr(NCS)2(Me2tn)2]+ cations (2 and 3), one cis-[Cr(NCS)4(Me2tn)]− anion (4), one NaSCN salt and one isopropyl alcohol molecule. In two independent complex cations, the chromium(III) ions are coordinated by four N atoms of two chelating Me2tn and two NCS groups in a distorted octahedral geometry while the chromium(III) ion in cis-[Cr(NCS)4(Me2tn)]– has a distorted octahedral coordination with two N atoms of one Me2tn and four NCS groups. The two six-membered rings in trans-[Cr(NCS)2(Me2tn)2]+ cations adopt both anti chair-chair conformations. The Cr–N(Me2tn) bond lengths range from 2.0624(18) to 2.0877(16) Å, while the Cr–N(NCS) bond lengths range from 2.0718(16) to 2.0428 (16) Å. The crystal lattice is stabilized by hydrogen bonding interactions among the NH groups of the Me2tn ligand, OH group of i-PrOH and the S atoms of the NCS groups. The infrared spectral properties are also described.